Glucocorticoid treatment earlier in childhood and adolescence show dose‐response associations with diurnal cortisol levels. Issue 8 (9th September 2017) - Vestergaard, Martin; Holm, Sara K.; Uldall, Peter; Siebner, Hartwig R.; Paulson, Olaf B.; Baaré, William F.C.; Madsen, Kathrine S.
Abstract: Heightened levels of glucocorticoids in children and adolescents have previously been linked to prolonged changes in the diurnal regulation of the stress‐hormone cortisol, a glucocorticoid regulated by the hypothalamic‐pituitary‐adrenal‐axis (HPA‐axis). To address this question, we examined the salivary cortisol awakening response (CAR) and daily cortisol output in 36 children and adolescents (25 girls/11 boys) aged 7–16 years previously treated with glucocorticoids for nephrotic syndrome or rheumatic disorder and 36 healthy controls. Patients and controls did not significantly differ in the CAR or diurnal cortisol output; however, sex‐dependent group differences were observed. Specifically, female patients had a higher CAR relative to female controls, while male patients had higher daily cortisol levels compared to male controls. Notably, CAR in female patients and daily cortisol levels in male patients showed a positive linear relationship with the mean daily glucocorticoid doses administered during treatment. The observed dose‐response associations suggest that glucocorticoid therapy during childhood and adolescence might trigger long‐term changes in HPA‐axis regulation, which may differ for males and females.